2021
DOI: 10.15548/jk.v11i1.420
|View full text |Cite
|
Sign up to set email alerts
|

Perlindungan Hak-Hak Perempuan Melalui Kepemilikan Harta Warisan Menurut Hukum Islam

Abstract: Islam teaches equality between men and women, without any differences, except in matters of nature alone. The presence of Islam brings goodness to women who were previously oppressed by the jahiliyah culture which did not recognize their position as perfect human beings like men. This research is important to do to answer the views that have been cornering Islam, that women are being looked down on and positioned as dishonorable, but it is the opposite. This research is normative-qualitative in nature by refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Hence, the knowledge management system is a crucial factor in creating a correlative relationship with employees' job satisfaction in an organization; therefore, exploring and examining the impact of knowledge management on academic staff satisfaction is always a topic of interest to management scientists. When knowledge management impacts work happiness, improved knowledge management applications might boost lecturers' satisfaction (Hasballah, 2021). Knowledge management may be used to solve organizational difficulties, thereby reaching the desired objectives and vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the knowledge management system is a crucial factor in creating a correlative relationship with employees' job satisfaction in an organization; therefore, exploring and examining the impact of knowledge management on academic staff satisfaction is always a topic of interest to management scientists. When knowledge management impacts work happiness, improved knowledge management applications might boost lecturers' satisfaction (Hasballah, 2021). Knowledge management may be used to solve organizational difficulties, thereby reaching the desired objectives and vision.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a direct and correlated relationship between knowledge management and employees' job satisfaction. Knowledge management systems must overcome organizational difficulties, including employee confrontations and job satisfaction (Hasballah, 2021). Knowledge management is considered a fundamental factor in increasing the satisfaction level of an organization; the application of elements in the knowledge management process helps shape the interaction between employees and take advantage of the knowledge resources of the involved personnel within the organization, thereby achieving high performance at work and leading to satisfaction with their assigned work (Meher & Mishra, 2021).…”
Section: Hypothesis and Conceptual Modelmentioning
confidence: 99%